2014
DOI: 10.1038/nsmb.2740
|View full text |Cite
|
Sign up to set email alerts
|

The ABC-F protein EttA gates ribosome entry into the translation elongation cycle

Abstract: ABC-F proteins have evaded functional characterization even though they comprise one of the most widely distributed branches of the ATP-binding cassette (ABC) superfamily. Herein, we demonstrate that YjjK, the most prevalent eubacterial ABC-F protein, gates ribosome entry into the translation elongation cycle through a nucleotide-dependent interaction sensitive to ATP/ADP ratio. Accordingly, we rename this protein Energy-dependent Translational Throttle A (EttA). We determined the crystal structure of Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
253
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(271 citation statements)
references
References 77 publications
16
253
2
Order By: Relevance
“…An ~70-residue ‘linker’ motif, unique to ABC-F proteins lies between the tandem NBDs and contains an extended α-helix. Overall, the protein adopts an ‘open’ conformation, with the subdomains organized loosely with respect to one another, as expected for an ABC protein without a bound nucleotide 1 .…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…An ~70-residue ‘linker’ motif, unique to ABC-F proteins lies between the tandem NBDs and contains an extended α-helix. Overall, the protein adopts an ‘open’ conformation, with the subdomains organized loosely with respect to one another, as expected for an ABC protein without a bound nucleotide 1 .…”
mentioning
confidence: 58%
“…Two new reports describe the discovery of a bacterial protein factor, energy-dependent translation throttle A (EttA), which can regulate translation in response to changes in cellular energy homeostasis 1 , 2 . The ability of EttA to link protein synthesis to changing metabolite levels opens up the exciting possibility that other translation factors might also respond to different physiological cues, as is the case for transcriptional regulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that ARE proteins might interact with the ribosome and affect the binding of antibiotics to their target site (17). Very recently, the function of the first ABC-F protein, EttA, as a translation factor which regulates protein synthesis depending on cell energy status has been characterized (19,20). The similarity of Vga(A)* to EttA (31% identity) allows us to envisage a mechanism of Vga(A) action based on the EttA one, providing a more-detailed insight into the probable involvement of Vga(A) in antibiotic resistance by ribosome protection than ever before.…”
mentioning
confidence: 99%